Riot, Calm & Luxury. - The Power Plant, Toronto (Toronto : The Art Gallery at Harbourfront, 1985)
Andrews, Stephen ; Baird, Rebecca ; Banks, Richard ; Benner, Ron ; Caines, Derek ; Choi, Pauline ; Cook, Sharon ; Gawad, Adly ; Hassan, Jamelie ; Johnson, Rae ; Keeley, Shelagh ; Merrill, Michael ; Quigley, Warren ; Runt ; Wilson, Tony
Riot, Calm & Luxury, The Art Gallery at Harbourfront, Toronto
Engels
kunstcatalogus